Pengaruh Gaya Kepemimpinan Tranformasional, Motivasi Intrisik, dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan - Septian Aris Munandar; Prayekti Prayekti (EBBANK, 2020)
The purpose of this study was to determine the effect of transformational leadership style, intrinsic motivation, and work environment simultaneously and partially on employee job satisfaction of Waroeng SS Jln. Bantul. The population of this research are Waroeng SS employees, Jln. Bantul with 40 employees. The sampling technique is saturated or census sampling by taking a sample of 40 employees. Data collection method with questionnaire. The analysis technique used is simple regression with a significance level of 0.05. The results of this study indicate that transformational leadership, intrinsic motivation, and work environment simultaneously influence job satisfaction. Transformational leadership, intrinsic motivation, and work environment have a positive and significant effect on employee job satisfaction.